STRUKTUR GRAMATIKAL PADA BERITA NASIONAL DI CNN INDONESIA.COM EDISI JUNI 2021 (TINJAUAN SINTAKSIS) - Riska Pratiwi; Roni Nugraha Syafroni; Suntoko (Universitas Wiralodra, 2022)
Abstract This study aims to determine the grammatical usability through syntactic and journalistic language reviews on the national news on CNN Indonesia.com June 2021 edition. This study uses a qualitative descriptive method. The results of this study show that there are 118 sentences, 149 clauses, 194 phrases, in short journalistic language features, abbreviations are found in 26 sentences (30 clauses), in solid journalistic language characteristics, 2 data are found that do not use the element where in news writing, in journalistic language characteristics. In simple simple sentences, 93 single sentences were found, the use of straightforward journalistic language features was found in the entire data, the use of interesting journalistic language features was found in the entire data, 15 reordering clauses were found and 31 clauses were incomplete in clear journalistic language features. Based on the data obtained, the researcher concludes that writing national news on CNN Indonesia.com still pays attention to the grammatical order when viewed syntactically and in journalistic language. Abstrak Penelitian ini bertujuan untuk mengetahui ketergunaan gramatikal melalui tinjauan sintaksis dan secara bahasa jurnalistik pada berita nasional di CNN Indonesia.com edisi Juni 2021. Penelitian ini menggunakan metode deskriptif kualitatif. Hasil dari penelitian ini menunujukkan terdapat 118 kalimat, 149 klausa, 194 frase, dalam ciri bahasa jurnalistik singkat ditemukan penyingkatan pada 26 kalimat (30 klausa), ciri bahasa jurnalistik padat ditemukan 2 data yang tidak menggunakan unsur where pada penulisan berita, pada ciri bahasa jurnalistik sederhana ditemukan kalimat tunggal sebanyak 93 kalimat, ditemukannya penggunaan ciri bahasa jurnalistik lugas pada keseluruhan data, ditemukannya penggunaan ciri bahasa jurnalistik menarik pada keseluruhan data, ditemukannya 15 klausa susun balik dan 31 klausa tidak lengkap pada ciri bahasa jurnalistik jelas. Berdasarkan data yang didapat peneliti menyimpulkan jika penulisan berita nasional di CNN Indonesia.com masih memperhatikan tatanan gramatikal jika ditinjau secara sintaksis dan bahasa jurnalistik.